Synthesis of Dibenzylidene Acetone via Aldol Condensation of Diacetone Alcohol with Substituted Benzaldehydes - Kulkarni, Pramod; Totre, Ganesh (Orbital: The Electronic Journal of Chemistry, 2019)
Aldol condensation between diacetone alcohol and substituted benzaldehyde using calcium hydroxide as a base was investigated. Reaction of diacetone alcohol with benzaldehyde in the presence of base formed 4-benzylidene-5-hydroxy-5-methyl-1-phenylhex-1-en-3-one, which then converted into dibenzylidene acetone. The advantages of this method include high yield, use of inexpensive catalyst, easy workup, and simple purification process. DOI: http://dx.doi.org/10.17807/orbital.v11i5.1388